COMPUTER IMPLEMENTATION OF RECURRENCE ALGORITHMFOR COMB TENSIONING DEVICE SQUARE MACHINES - SHCHERBAN, VOLODYMYR; KOLISKO, OKSANA; KOLISKO, MARJANA; KIRICHENKO, ANTON; SHCHERBAN, YURYJ (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Computer implementation of the recursion algorithm allows at the initial stage to determine the thread tension, which occurs after passing the comb tension device of the hosiery feed system depending on the physical and mechanical properties of raw materials, geometric parameters of structural elements of the hosiery thread feed system. Computer determination of the change in relative tension on stocking machines is based on the use of the dichotomy algorithm in solving transcendental equations.Determining at the initial stage of the tension of the thread feed process on hosiery machines allows to determine the tension after passing the comb tensioning device, which will occur during the interaction of the thread with the structural elements of the cylindrical comb tension device depending on the type of raw material, curvature for bending, deformation in the area of ​​contact with the guide, the feed rate of the thread. The increase in tension after passing the comb tensioning device is due to the increase in friction between the thread and the cylindrical guide. This is due to the increase in the coverage angles of the cylindrical guide rods of the comb tensioning device. The development of a computer program for determining the tension of the thread on stocking machines should be based on the use of object-oriented programming languages. Determining the tension and changes in relative tension in the refueling zones of hosiery machines, taking into account the specifics of the design of the thread feed system of hosiery machines, will reduce thread breakage, optimize thread tension in the working area of ​​hosiery machines.The improvement of the technological process of thread processing on hosiery machines should be based on theoretical and experimental studies of the process of interaction of threads with structural elements of the feed system, including comb tensioning device and guides of large and small curvature. The main element of the structural elements of the feed system of stocking machines is a comb device for tension. Theoretical dependences for determining the tension after the comb device will allow to obtain algorithmic and mathematical software, which is used in computer software to calculate the tension and change the relative tension in the areas of refueling stocking machines. Optimization of tension in the working area will reduce the change in relative tension in the refueling areas of hosiery machines, improve the quality of hosiery.
Keywords: recursion algorithm; computer program; thread feed system; stocking machine